The Role of Purinergic Signaling in Heart Transplantation - Jiang, Yanzhi; Lin, Jianxin; Zheng, Haiyun; Zhu, Ping (Frontiers in Immunology, 2022)
Heart transplantation remains the optimal treatment option for patients with end-stage heart disease. Growing evidence demonstrates that purinergic signals mediated by purine nucleotides and nucleosides play vital roles in heart transplantation, especially in the era of ischemia-reperfusion injury (IRI) and allograft rejection. Purinergic signaling consists of extracellular nucleotides and nucleosides, ecto-enzymes, and cell surface receptors; it participates in the regulation of many physiological and pathological processes. During transplantation, excess adenosine triphosphate (ATP) levels are released from damaged cells, and driver detrimental inflammatory responses largely via purinergic P2 receptors. Ecto-nucleosidases sequentially dephosphorylate extracellular ATP to ADP, AMP, and finally adenosine. Adenosine exerts a cardioprotective effect by its anti-inflammatory, antiplatelet, and vasodilation properties. This review focused on the role of purinergic signaling in IRI and rejection after heart transplantation, as well as the clinical applications and prospects of purinergic signaling.